MICROBIAL DEGRADATION OF ENDOSULFAN IN AGRICULTURAL SOILS - B.S. Ismail; A.O.S. Enoma (Universitas Gadjah Mada, 2005)
A study of the degradation of endosulfan (6, 7, 8, 9, 10, 10-hexachloro – 1, 5, 5a, 6, 9, 9a –hexahydro – 6, 9- methano – 2, 4, 3 – benzodioxanthiepin 3 – oxide) in Malaysian sandy loam and clay soils was carried out using a radioisotopic technique under laboratory conditions. It was demonstrated that endosulfan possessed long half-lives of 433, 495 and 462 days in aerobic sandy loam, aerobic clay and anaerobic clay soils respectively. Endosulfan degrades faster in non-sterile than in sterile soils. This study indicates that microorganisms are involved in the degradation of endosulfan. In general, degradation of the pesticide was relatively higher in the clay soil than in the sandy soil. Apart from the parent compounds, ?- and ?-isomers, the degradation products include endosulfan sulphate and three minor unidentified products.